The histogenesis of cranial cava veins under influence of ethanol. - A. U. Gadjieva (Морфологія, 2014)
Background. The structural changes in veins are influenced by a variety of chemicals, including ethanol. Effect of ethanol is primarily manifested in violation of structures of blood vessels and heart. Objective. To detect changes of morphological and functional features of intrapericardial division of the cranial venae cavae in 132 rats aged 1-30 days when exposed to ethanol. Methods. 60 rats received milk with ethanol in lactation period from females which were intraperitonealу injected 40° ethanol in a dose of 8 ml/kg from 2 to 22 day. 72 intact rats were used as controls. Results. As a result of the experiment reduction of the wall thickness of intrapericardial part of the cranial venae cavae and violation of their growth were observed. Conclusion. Admission of ethanol with maternal milk results in the thickening of the collagen and elastic fibers, destruction of reticular fibers, muscle cells and endothelial cells.